Experimental Study on the Seismic Behavior of All-Steel Buckling-Restrained Braces Without an Unbonded Material Layer - Kechuan Wu; Guanglan Wei; Longfei Zhang; Wenzheng Yu; Xiang Lan (Buildings)
Three all-steel buckling-restrained brace (ABRB) specimens without unbonded materials were designed and manufactured. Through low-cycle reciprocating load tests, the seismic performance of these buckling-restrained braces was investigated, and the influence of the absence of an unbonded layer on failure modes, energy dissipation capacity, and low-cycle fatigue life was examined. The research findings suggest that in all-steel buckling-restrained braces lacking an unbonded layer, the excessive friction between the energy dissipation unit and the restraining unit can, to a certain degree, increase local compressive stress. This makes the braces more susceptible to local buckling at the ends. The frictional effect causes the axial force of the ABRB to follow a distribution pattern where it is greater at the ends and smaller in the middle. Correspondingly, the buckling wavelength of the energy dissipation unit shows a pattern of being shorter at the ends and longer in the middle, which also results in a significant cyclic hardening phenomenon in the ABRB. The fatigue performance of the ABRB is inversely related to the amplitude of local buckling in the energy dissipation unit.